The use of dietary supplements by the elderly - Oskędra, Iwona; Broszkiewicz, Broszkiewicz; Zych, Beata Ewa (Nursing in the 21st Century, 2015)
THE USE OF DIETARY SUPPLEMENTS BY THE ELDERLYIntroduction. Life expectancy has expanded – both due to lifestyle changes and medical achievements. Constant health care is required in every aspect in order to maintain its high quality.Aim. Assessing of elderly persons’ interest in the use of food supplements.Material and methods. The study covered a group of 100 men and women, 60-80 years of age. The method of diagnostic survey was used; the tool was a 28-point questionnaire prepared by the authors.Results. Ninety one per cent of the respondents confirmed taking dietary supplements. A substantial group (58%) of the respondents was convinced about their beneficial influence on human health, and 21% did not think it was necessary to use the sesupplements. More than 50% of the respondents used the preparations because they cared for their health. Most of the respondents noticed positive effects of the supplements, such as: an increase of vitality and resistance to diseases, better functioning of the organs of movement. Most respondents purchased the supplements in pharmacies. The use of supplements is perfectly safe in the opinion of 45% of the study group while 28% think it may carry some risks.Conclusion. The most frequent motivations of diet supplementation was boosting resistance and vitality, supplement irondeficiency, stress management. Diet supplements were used by more women (94.8%) than men (85.7%) and more healthy people(96.9%) than the sick (88.2%) but the difference was not statistically significant.